Factor structure and measurement invariance across groups of the Italian Eysenck Personality Questionnaire - Short form (EPP-S). (1st March 2018) - Picconi, Laura; Jackson, Chris J.; Balsamo, Michela; Tommasi, Marco; Saggino, Aristide
Abstract: The Eysenck Personality Profiler (EPP; Eysenck, Barrett, Wilson, & Jackson, 1992) measures traits at both the super factor level and the primary scale level, yielding three super factors (Extraversion, Neuroticism, and Psychoticism) and 21 primary scales, as well as a Lie scale. The Eysenck Personality Profiler-Short (EPP-S) is a direct development of the EPP. The primary scales of the EPP-S were examined in a sample of 1304 subjects (53.5% females), with mean age of 40.6 years, first, to determine their factor structure. Confirmatory factor analysis showed that the EPP-S fits a three factor structure reasonably well. Second, results provide evidence that support the gender and age invariance. Woman are higher on N scales, males on P and E scales. E and P appeared to increase in young adults, while N decrease (Eysenck, Wilson, & Jackson, 2000). Our results suggest the EPP-S can provide measures of personality traits that are not overly affected by individual characteristics such as gender or age. Highlights: Factor structure and measurement invariance of the EPP-S is proposed. A sample of 1394 subjects, from 17 to 84 years old The three factor structure showed a reasonable fit to the data. Results provide evidence that support the gender and age invariance.